DNA Hypermethylation in Somatic Cells Correlates with Higher Reprogramming Efficiency123. (24th July 2012) - Barrero, María J.; Berdasco, María; Paramonov, Ida; Bilic, Josipa; Vitaloni, Marianna; Esteller, Manel; Belmonte, Juan Carlos Izpisua
Abstract: The efficiency of somatic cell reprogramming to pluripotency using defined factors is dramatically affected by the cell type of origin. Here, we show that human keratinocytes, which can be reprogrammed at a higher efficiency than fibroblast [Nat Biotechnol 2008;26:1276‐1284], share more genes hypermethylated at CpGs with human embryonic stem cells (ESCs) than other somatic cells frequently used for reprogramming. Moreover, pluripotent cells reprogrammed from keratinocytes (KiPS) are more similar to ESCs than those reprogrammed from fibroblasts (FiPS) in regard to DNA methylation levels, mostly due to the presence of genes that fail to acquire high levels of DNA methylation in FiPS cells. We propose that higher reprogramming efficiency correlates with the hypermethylation of tissue‐specific genes rather than with a more permissive pluripotency gene network. STEM CELLS 2012;30:1696–1702